Transition : Paying for a Shift from Pay-as-You-Go Financing to Funded Pensions - World Bank (World Bank, Washington, DC, 2012)
There is a widespread perception that public pension systems in richer countries are in crisis. As schemes mature and the population ages, the burden of financing pensions has grown and, on current policies, will rise much further. Developing countries are younger and pension systems relatively immature. But the transformation in demographics and pension benefits that took over a century in richer nations is forecast to take less than 30 years in developing economies. The Bank has argued that a 'three-pillar' pension system can mitigate emerging problems in developing countries' public pension systems. The recommended system, set out in Averting the Old Age Crisis consists of 'a publicly managed system with mandatory participation and the limited goal of reducing poverty among the old; a privately managed mandatory savings system; and voluntary savings'. The note compares funded and pay-as-you-go finance of retirement incomes, highlighting the transition double burden, and, stipulates size of the transition will depend on the starting point: How generous is the current pay-as-you-go pension promise? How mature is the pay-as-you-go pension system? What is the age structure of the population? Transition costs can be controlled by a number of policies: Limiting the coverage of the funded program to new labor-market entrants or younger workers spreads the transition cost over a longer period; Scaling down existing pay-as-you-go liabilities is likely to play an important part in any fundamental pension reform; Governments can share in any extra returns to the funded system and use them to help pay for the transition cost. Countries have in practice used a mix of strategies. The precise balance between debt and budgetary finance (spending cuts or tax increases) should be chosen in the general context of a country's fiscal policy.